Monetary policy, asset prices and consumption in China - Tuuli Koivu (Bank of Finland, Institute for Economies in Transition (BOFIT), 2010)
This paper studies the wealth channel in China. Using the structural vector autoregression method, we find that a loosening of China.s monetary policy indeed leads to higher asset prices, which in turn are linked to household consumption. However, the importance of the wealth channel as a part of the monetary policy transmission mechanism in China is still limited.
URN:NBN:fi:bof-201408072125
Keywords: E52; P24; 330; China; monetary policy; asset prices